Incidence of vaccine preventable diseases in pediatric population of Latvia - Renāta Klagiša; Anija Meiere (Social Welfare: Interdisciplinary Approach)
Childhood and adolescent immunizations are one of the most effective means of preventing such serious diseases as diphtheria, pertussis, rubella etc. These infectious diseases are termed as vaccine preventable diseases because vaccination continues to be the most effective strategy to reduce morbidity and mortality from these diseases. Despite this, immunization is an emotional issue for many parents. As vaccine preventable diseases become less common and parents have little familiarity with the devastating effects of vaccine preventable illnesses, the benefits of immunization may seem less important than the potential adverse effects.